2008
DOI: 10.1083/jcb.200712086
|View full text |Cite
|
Sign up to set email alerts
|

EPB41L5 functions to post-transcriptionally regulate cadherin and integrin during epithelial–mesenchymal transition

Abstract: EPB41L5 belongs to the band 4.1 superfamily. We investigate here the involvement of EPB41L5 in epithelial–mesenchymal transition (EMT) during mouse gastrulation. EPB41L5 expression is induced during TGFβ-stimulated EMT, whereas silencing of EPB41L5 by siRNA inhibits this transition. In EPB41L5 mutants, cell–cell adhesion is enhanced, and EMT is greatly impaired during gastrulation. Moreover, cell attachment, spreading, and mobility are greatly reduced by EPB41L5 deficiency. Gene transcription regulation during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(112 citation statements)
references
References 48 publications
7
104
1
Order By: Relevance
“…Previous work demonstrated that EPB41L5 was required during early embryo gastrulation, which seemed to be partially a result of EPB41L5-dependent FA modulation and cell-cell contact establishment via cadherins (37). On the basis of our observations, we here propose that EPB41L5 mainly influences the maturational phase of FAs, implicating that decreased tension or traction might attribute for the detachment of podocytes, as evidenced in the EPB41L5 knockout model (Figs.…”
Section: Discussionsupporting
confidence: 77%
“…Previous work demonstrated that EPB41L5 was required during early embryo gastrulation, which seemed to be partially a result of EPB41L5-dependent FA modulation and cell-cell contact establishment via cadherins (37). On the basis of our observations, we here propose that EPB41L5 mainly influences the maturational phase of FAs, implicating that decreased tension or traction might attribute for the detachment of podocytes, as evidenced in the EPB41L5 knockout model (Figs.…”
Section: Discussionsupporting
confidence: 77%
“…Ngn3-positive cells are still epithelial cells expressing Ecadherin. E-cadherin is known to be a very stable protein and has to be regulated both at the protein and the transcriptional levels to efficiently promote EMT (Arnold et al, 2008;Hirano et al, 2008;Zahn et al, 2008). Therefore, subtle changes in E-cadherin may have already started but are not detectable yet.…”
Section: Discussionmentioning
confidence: 99%
“…6B). In the absence of known pancreas progenitor cell lines, this epithelial cell line was chosen based on its robust endogenous E-cadherin expression and its common use as an EMT model (Miettinen et al, 2000;Hirano et al, 2008). Known repressors of E-cadherin such as Snail1 and Snail2 could efficiently repress transcription of E-cadherin when compared with control transfection (Fig.…”
Section: E-cadherin Is Transcriptionally Regulated In Endocrine Cellsmentioning
confidence: 99%
“…This indirect effect of p120cate-nin could be cell-type specific as the expression of a p120catenin mutant unable to regulate RhoA in endothelial cells has no effect on VE-cadherin endocytosis [52]. Finally, cadherin-bound p120catenin associates with FERM-domain containing proteins (EPB4125 and FRMD5) that modulate cadherin stability at the plasma membrane [61,62].…”
Section: Membrane-associated P120catenin and The Regulation Of Adherementioning
confidence: 99%